ETIKA PELAYANAN PUBLIK BAGI PENYANDANG DISABILITAS DI KECAMATAN CURUG KABUPATEN TANGERANG - nafiah, idhotun123 (Universitas Tulungagung, 2026)
this research aims to analyze the ethical of public services in curug district, tangerang regency. public services are the government's efforts to fulfll the basic needs and civil rights of every citizen, but are often faced with erhical problems that result in public dissatisfaction. researchers used descriptive qualitative analysis methods by conducting observations and interviews to identify obstacles and strategies in improving the quality of public services, especially for people with disabilities. the research results show that there is no discrimination in service. the prinsiple of service ethics as the curug district office are in accordance with the service ethics theory (surahman, 2020), namely quality, professional service and meeting the needs of service recipients. it is hoped that this research can contribute to the development of public service ethics in curug district.